Hall Screens for Gymnastics Competitions - Lamelas, Cláudio André Rodrigues (2023)
This document presents an engineering project developed in Acro Companion, a company specialized in gymnastics software. This project is important to Acro Companion’s flagship product, an application designed to streamline gymnastics competitions for organizers, coaches, judges, and gymnasts. The platform automates various aspects of competition management, real-time scoring, club membership, and display control in competition venues. The project’s focus was on improving the Scoring service, particularly the Hall Screens area, responsible for displaying and controlling real-time information on the competition’s screens. The problems plaguing the Hall Screens diverge into two distinct categories. In the first category are the inadequacies in the scoring screen’s architectural design, hampering maintainability, enhancements and the diversification of the view types. The second category, related to the controller mechanism, is the lack of this mechanism in power, reactivity and usability, which ends up disrupting the user’s workflow. This project rallies around three primary objectives. Leveraging UI designs as blueprints, the first objective was to re-imagine the Hall Screens, fostering new designs and better architectural foundations to enhance maintainability, correct behaviour and expansion potential. The second objective is the development of a new powerful and reactive solution for the mechanism that controls the screens. The last objective is the development of a suite of end-to-end tests specific to the Hall Screens area to ensure reliability and correctness. The results of this project were significant. The Hall Screens component improved significantly in terms of stability, robustness, and architectural organization. Simultaneously, the new controller mechanism, though not feature-complete, was entirely reinvented, enhancing maintainability, understandability, reactivity and user experience. Additionally, a large suite of end-to-end tests was implemented, improving the overall stability of the Hall Screens and increasing safety during development. In summary, this project within Acro Companion tackled critical issues in their gymnastics competition platform, resulting in substantial improvements to the Hall Screens, Controller Mechanism, and overall system stability. These enhancements contributed to the company’s mission of providing efficient solutions for gymnastic competitions.